Peri-operative management of percutaneous fetoscopic spina-bifida repair: a descriptive review of five cases from the United Kingdom, with focus on anaesthetic implications. (August 2020) - Goonasekera, C.D.; Skelton, V.A.; Zebian, B.; Nicolaides, K.; Araujo Lapa, D.; Santorum-Perez, M.; Bleil, C.; Hickey, A.; Bhat, R.; Oliva Gatto, B.E.
Highlights: Percutaneous fetoscopic spina bifida repair under general anaesthesia is safe. Fetal well-being can be assessed by umbilical artery pulsatility index. Intravenous anaesthesia and inhaled sevoflurane provide reversible tocolysis. Transplacental anaesthesia achieves adequate fetal anaesthesia and immobilisation. Intra-uterine pressure during CO2 inflation best maintained near 'opening' pressure. Abstract: We present a case-based review of the first five percutaneous fetoscopic in-utero spina bifida repair procedures undertaken in the UK. Our focus is on implications of anaesthesia and analgesia for the mother and fetus, provision of uterine relaxation and fetal immobilisation while providing conditions conducive to surgical access. Minimising risks for fetal acidosis, placental and fetal hypoperfusion, maternal and fetal sepsis and maternal fluid overload were the foremost priorities. We discuss optimisation strategies undertaken to ensure fetal and maternal well-being under anaesthesia, shortcomings in the current approach, and possible directions for improvement.